Structural,morphological,and optical properties of tin(Ⅳ) oxide nanoparticles synthesized using Camellia sinensis extract: a green approach - Selvakumari, J. Celina; Ahila, M.; Malligavathy, M.; Padiyan, D. Pathinettam (International journal of minerals, metallurgy and materials, 2017)
Tin oxide（SnO2） nanoparticles were cost-effectively synthesized using nontoxic chemicals and green tea（Camellia sinensis） extract via a green synthesis method. The structural properties of the obtained nanoparticles were studied using X-ray diffraction, which indicated that the crystallite size was less than 20 nm. The particle size and morphology of the nanoparticles were analyzed using scanning electron microscopy and transmission electron microscopy. The morphological analysis revealed agglomerated spherical nanoparticles with sizes varying from 5 to 30 nm. The optical properties of the nanoparticles’ band gap were characterized using diffuse reflectance spectroscopy. The band gap was found to decrease with increasing annealing temperature. The O vacancy defects were analyzed using photoluminescence spectroscopy. The increase in the crystallite size, decreasing band gap, and the increasing intensities of the UV and visible emission peaks indicated that the green-synthesized SnO2 may play future important roles in catalysis and optoelectronic devices.